The Impact of Fintech Payments and Financial Literacy on Student Financial Management Behaviour - Khotimah, Khusnul; Puspitasari, Intan; Galih Prasaja, Mahendra (UMSurabaya Publishing, 2025)
This study aims to ascertain how much fintech payments and financial literacy influence the money management behaviors of Muhammadiyah University Purworejo students. Students at the Muhammadiyah University Purworejo Class of 2019–2021 served as the research population. Using non-probability sampling approaches and a quantitative methodology, 318 respondents made up the study's sample. Multiple linear regression analysis approaches are used for initial data processing in SPSS version 25 (Statistical Package for Social Science). The study's findings demonstrate that students' money management practices are significantly and favorably impacted by financial literacy to some extent. Fintech payments significantly and advantageously impact how students handle their finances. Financial literacy and fintech payments simultaneously have a significant, positive impact on students' money management practices. You can effectively manage your fintech payment usage and make wiser and more fruitful future financial decisions if you thoroughly understand money